Pharmacokinetic and ocular microdialysis study of oral ginkgo biloba extract in rabbits by UPLC-MS/MS determination. (15th August 2017) - Wang, Shuya; Li, Ding; Pi, Jiaxin; Li, Wen; Zhang, Bing; Qi, Dongli; Li, Nan; Guo, Pan; Liu, Zhidong
Abstract: Objectives: The purpose of this work was to determine and investigate the absorption of ginkgo terpenoids (GT) in plasma and aqueous humour after oral administration of ginkgo biloba extract (GBE) by UPLC-MS/MS method. Methods: The UPLC-MS/MS determination of GT employed the multiple reaction monitoring mode using an electrospray negative ionization. The rabbits were orally administered the suspension of GBE at a dose of 500 mg/kg. Serial plasma and dialysate samples were collected at the corresponding time and then analysed by UPLC-MS/MS. Key findings: In plasma, the mean AUC from 0 to 48 h was 14.12, 12.59, 23.75, 1.51 h μg/ml for GLJ and 5.34 h μg/ml for GLA, GLB, GLC, GLJ and BLL, respectively. In aqueous humour, the five ginkgo terpenoids have been detected. Compared with the other four GT, BLL has better absorption in the eyes. Conclusions: A selective and reproducible UPLC-MS/MS method was developed and validated to determine and investigate the absorption of ginkgo terpenoids in plasma and aqueous humour of rabbits after oral administration of GBE. The main five ginkgo terpenoids could be absorbed into eyes.